The effect of verapamil on mitochondrial calcium content in normoxic, hypoxic and reoxygenated rat liver - Konrad, Thomas; Beier, Konstantin; Kusterer, Klaus; Juchem, Rolf; Usadel, Klaus H.; Angermüller, Sabine (The histochemical journal, 1997)
Calcium channel blockers protect cells against ischaemia-reperfusion injury. In the present study, the effect of verapamil on mitochondrial calcium content was investigated in situ in normoxic, hypoxic and reoxygenated rat liver. Subcellular distribution of exchangeable calcium ions, which form an electron-dense precipitate with antimonate, was demonstrated with the glutaraldehyde-osmium antimonate technique. Calcium precipitates were quantified morphometrically using automatic image analysis. In normoxic liver, the mitochondrial calcium content formed a gradient decreasing from the periportal to perivenous regions. The low mitochondrial calcium content in perivenous regions remained unaffected in all experimental conditions. In hypoxic and reoxygenated liver, the calcium content in mitochondria of the periportal areas was significantly reduced. Verapamil pretreatment levelled the calcium gradient in normoxic liver by reducing the periportal calcium content. Verapamil had no effect on the mitochondrial calcium content in hypoxic liver. In contrast, in verapamil-pretreated reoxygenated liver, the mitochondrial calcium content in periportal mitochondria increased significantly, thus restoring the zonal calcium gradient. In conclusion, these data suggest that modulations of mitochondrial calcium content in the periportal region of the liver lobule may play an important role in the protective effects of verapamil against ischaemia-reperfusion injury